2021
DOI: 10.1108/jedt-04-2021-0205
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting BIM implementation in post-conflict low-income economies: the case of Afghanistan

Abstract: Purpose Rejecting building information modeling (BIM) can negatively impact the architectural, engineering and construction (AEC) industries. While BIM is trending globally, its implementation in post-conflict low-income economies is still limited. The purpose of this paper is to identify the critical factors for implementing BIM in a post-conflict low-income economy, using Afghanistan as a case study. Design/methodology/approach This study identifies potential affecting factors for BIM implementation throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Furthermore, rather than representing the population, the objective of this study was to focus on the relative importance of the success factor. This objective has been set per prior works, such as those that identified the most critical elements affecting the adoption of construction innovations [19,38]. As a result, the sample size was deemed sufficient for this study.…”
Section: Collecting Survey Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, rather than representing the population, the objective of this study was to focus on the relative importance of the success factor. This objective has been set per prior works, such as those that identified the most critical elements affecting the adoption of construction innovations [19,38]. As a result, the sample size was deemed sufficient for this study.…”
Section: Collecting Survey Datamentioning
confidence: 99%
“…The emphasis should be on developing smoothly, moving from newer approaches to more established ones. This will ensure that there is less resistance to change, less requirement for training, and a more rapid transition [38].…”
Section: Positive Legislation Toward Concrete Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, researches (Al-Mohammad et al, 2021;Cooney et al, 2021;Evans et al, 2021;Gharouni Jafari et al, 2021;Saka and Chan, 2021;Silverio and Suresh, 2021;Tai et al, 2021) have revealed that the delay drivers that impact non-BIM-based and BIM-based construction projects are not necessarily the same. This is due to a variety of reasons, including the adoption of BIM for accurate geometric model development within the continuum modelling strategy (Kassotakis and Sarhosis, 2021), ability to integrate BIM with emerging radio frequency identification technologies in structural engineering (Duan and Cao, 2020), use of BIM to control the geometry of arch pylon as it is being built while taking into account seasonal temperature fluctuations (Wang et al, 2022), or since BIM now allows for the storage of modularisation data from past projects (Tidhar et al, 2021), and as argued by Johnston et al (2018) the weights of various structural forms are more readily available as a result of the increased usage of BIM and structural analysis models, and may be used to swiftly compute embodied carbon etc.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing how much of this knowledge is being transferred within organisations is important. Such knowledge justifies resource commitment and sustained innovation in construction organisations (Al-Mohammad et al, 2021;Zhou, Yang & Yang, 2019). Several studies discussed general knowledge transfer within the construction industry (Owusu-Manu et al, 2018;Saini, Arif & Kulonda, 2020;Yap & Toh, 2020).…”
Section: Introductionmentioning
confidence: 99%